Maduración esquelética de mano y muñeca y osificación de sutura media palatina en adolescentes: una revisión de literatura. - Ramirez-Diaz, Ruth Elizabeth (2023)
Introduction: The evaluation of skeletal age is an important factor in orthodontic planning to anticipate changes in growth, with the analysis of hand and wrist radiographs showing the degree of bone and facial growth potential. The objective was to evaluate the relationship between skeletal maturation of the hand and wrist and ossification of the midpalatal suture (MPS) in adolescents. Materials and methods: A search was carried out in four databases such as Pubmed, Scopus, Science Direct and Embase were reviewed until December 13, 2022. The included studies were descriptive and comparative articles on the skeletal maturation of the hand and wrist and ossification of the midpalatal suture of patients aged 7 to 18 years. Two researchers carefully selected the articles evaluated and analyzed the different key topics related to the topic. Results: Four articles were included in this study; According to the studies, it was found that the greater the degree of bone maturation there is an increase in the approximation of the SMP, especially in late stages, with high and positive correlations; Furthermore, there were greater evaluation results with the Fishman analysis method as opposed to the Hagg and Taranger and Björk methods. The critical limit stages in SMI7-9, a greater approach to the closure of SMP compatible with stage D-E was found. The completion of maturation in women occurs up to 2 years earlier than in men. Conclusions: Diagnostic evaluation methods using carpal analysis can be used for predictive evaluations of the maturation stage of SMP; However, the results were not absolute in all cases so they cannot be generalized.